A leitura literária no contexto acadêmico - Barreto, Damaris de Queiroz (2018)
This thesis aims to present the literary reading inserted in the perspective of the students of the postgraduate programs in Information Science of Ceará, namely, the Academic Master in Information Science of the Federal University of Ceará - PPGCI/UFC and the Professional Master's Degree in Librarianship of the Federal University of Cariri - PPGB/UFCA, seeking to understand the relationships established during the academic course between students and reading practices. This research has a qualitative and exploratory nature, based on the dialectical method and on the understanding that the reading practice is intrinsically linked to the social and cultural intricacies of the individuals in focus. Bibliographical research was used as a means to develop the theoretical contributions that interweave the themes of the reading. The chosen research instrument was a semi-structured interview because it provided greater freedom of expression and flexibility to the interviewee, a fundamental fact for the construction of the study. From the research carried out, it was possible to conclude that the entrance in the higher education causes progressive distance from the practices of literary reading, being its sources derived from different slopes, but starting from common discourses among the students.